2022
DOI: 10.1101/2022.05.19.491028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Narrowband gamma oscillations propagate and synchronize throughout the mouse thalamocortical visual system

Abstract: SummaryRhythmic oscillations of neural activity permeate sensory systems. Studies in the visual system propose that broadband gamma oscillations (30 – 80 Hz) facilitate neuronal communication underlying visual perception. However, broadband gamma oscillations within and across visual areas show widely varying frequency and phase, providing constraints for synchronizing spike timing. Here, we analyzed data from the Allen Brain Observatory and performed new experiments that show narrowband gamma (NBG) oscillatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 53 publications
4
12
0
Order By: Relevance
“…2a,c). Frozen noise drove highly repeatable time-locked sequences of action potentials in the recorded neurons, consistent with prior work 16,[40][41][42][43] (Fig. 2b, left).…”
Section: Balanced Bidirectional Optogeneticssupporting
confidence: 87%
“…2a,c). Frozen noise drove highly repeatable time-locked sequences of action potentials in the recorded neurons, consistent with prior work 16,[40][41][42][43] (Fig. 2b, left).…”
Section: Balanced Bidirectional Optogeneticssupporting
confidence: 87%
“…For consistency of our studies, in this study, we chose the HG frequency range as 50 to 150 Hz and divided it into two components: lower component of HG activity (LHG; 50 to 70 Hz) which is similar to the narrowband gamma oscillation in other studies, and higher component of HG activity (HHG; 70 to 150 Hz). The boundary of two components (70 Hz) was determined based on the frequency range of conventional gamma oscillation (30 to 70 Hz), a recent study (narrowband gamma oscillation: 50 to 70 Hz) (Shin et al, 2023), and visual inspection of our data. Note that slight changes in boundary frequency (65 to 75 Hz) did not significantly affect the main results.…”
Section: Resultsmentioning
confidence: 99%
“…A vision study suggested that narrowband gamma oscillation is strongest in layer IV and reflects the signal flow from the thalamus to the cortex (Saleem et al, 2017). Furthermore, a recent study suggested that narrowband gamma oscillations (50 to 70 Hz) propagate and synchronize throughout the thalamocortical visual system in mice (Shin et al, 2023). Consistent with previous vision studies, in the current somatosensory study, we observed that LHG power was strongest in layer IV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that narrow gamma oscillations propagate beyond V1, potentially serving as a key mechanism for coordinated spiking across the mouse visual system. (Shin et al., 2023), indeed, it has been reported that several neurons in LGN, V1, and higher visual areas showed tightly coordinated narrow gamma band spiking and a high likelihood for pairwise functional interactions.…”
Section: Introductionmentioning
confidence: 91%